EFFECTS OF DYSFUNCTIONAL FAMILIES ON PUBLIC SECONDARY SCHOOLS STUDENTS ACADEMIC PERFORMANCE IN HABASWEIN SUB COUNTY, WAJIR COUNTY, KENYA - OMAE, OMARE AMOS; Kathuri, Prof. Nephat J.; Kibaara, Dr. Tarsilla (IJRDO- Journal of Educational Research, 2018)
The family being one of the most fundamental units of the society has a bearing on one’s psychological, physical, emotional and spiritual wellbeing. Negative patterns of parental behaviour tend to be dominant in their children’s lives. Therefore, the purpose of this study was to find out the effects of dysfunctional families on secondary school students academic performance in Habaswein Sub County in Wajir County, Kenya. It specifically sought to determine the effects of parental conflicts, on the academic performance of secondary school students in the Sub County. The study was guided by Abraham Maslow’s Theory of Needs and Burke’s Identity Control Theory. Descriptive survey research design was used targeting 703 students and 72 teachers from public secondary schools in Habaswein Sub County. Systematic random sampling was used to obtain a sample size of 251 respondents who participated in the study. Data was collected by the researcher using questionnaires. Piloting of the questionnaires was done in order to assess validity and reliability of the instruments. Instruments reliability was determined using the test-retest method and reliability coefficients of above 0.70 was obtained. Data was analyzed with the aid of the Statistical Package for Social Sciences (SPSS) version 21.0. Descriptive statistics involving means, modes and standard deviations, and inferential statistical methods involving Pearson’s Product Moment correlation and multiple regression analysis, was used to analyze the data, which was then presented in tables. The findings revealed that frequent parental conflicts in dysfunctional families adversely affected their children’s academic performance in Habaswein Sub County. A good number of students hailing from such families eventually and often discontinued with school when their parents separated. It is recommended that education stakeholders in the area provide the schools with adequate counselling facilities so as to enable students experiencing conflict in their families to cope with the situation.